IMPLEMENTING VALUE LINE LEARNING STRATEGY IN INCREASING STUDENTS’ CRITICAL THINKING IN SPEAKING SKILL - Sudirman, Sudirman; Tawali, Tawali (Lembaga Penelitian dan Pendidikan Mandala, 2022)
implementing value line learning strategy in increasing students’ critical thinking in speaking skill This study is attempted to find out based problem learning as an appropriate strategy to help the students to increase critical thinking in speaking skill using value line learning strategy at second grade in SMA NW Pendem. The methods of the research applied are quantitative and qualitative approach research. The research concert class of second grade in SMA NW Pendem and the sample of the research are 23 students. To analyze the data, the researcher used observation sheet for the English teacher to found out the condition of teaching learning process when the value line was implemented and the observation sheet was used to found out the students improvement ability in learning from the research data found out the result of students score of speaking skill was 80.86(19%) and the students score of written in this research was 80.57(92%), it can be conclude that using value line learning strategy in English foreign language classroom at the second grade students of SMA NW Pendem in academic year 2020/2021.